Current scenario of diagnosis and treatment of attention-deficit/hyperactivity disorder (ADHD) in urban India: a pilot study. Issue 3 (12th August 2021) - Basu, Sandhya; Banerjee, Bidisha
Abstract : Purpose: The current literature on attention-deficit/hyperactivity disorder (ADHD) shows a tangled picture of its etiology and diagnosis. It directs at over-medicalization in ADHD cases due to the pharmaceutical-based models surrounding its treatment. Further, the authors observed the negligible reporting of India's ADHD scenario in the reviewed literature. Thus, this study aims to explore the status of ADHD in India's urban setting through a pilot study. Design/methodology/approach: Social constructivist viewpoint guided this study. The authors conducted the pilot in two phases: face-to-face semi-structured qualitative interviews with 11 mental health professionals in the first phase, and, in the second phase, five mental health professionals responded to an online survey with same questions. After qualitative analysis, four major themes were identified: participants' opinions on ADHD etiology, issues in diagnosis, social context of ADHD and alternatives to medication. Findings: The findings highlight the need to re-visit the ADHD narrative in the Indian context. These findings also emphasize future investigation on the medicalization of ADHD in India. Research limitations/implications: A countrywide epidemiological survey is required to explore the distribution of the disorder to standardize diagnosis and treatment procedures pan-India. This paper is an attempt to iron out the ADHD-related information that needs further exploration and research. Originality/value: With in-depth interviews of mental health professionals, the study explores the state of ADHD in an urban setting in India. Future research must build on the current findings to establish the etiological and diagnostic framework of ADHD.